2019
DOI: 10.3390/app9152980
|View full text |Cite
|
Sign up to set email alerts
|

An Intelligent Event-Sentiment-Based Daily Foreign Exchange Rate Forecasting System

Abstract: Financial time series analysis is an important research area that can predict various economic indicators such as the foreign currency exchange rate. In this paper, a deep-learning-based model is proposed to forecast the foreign exchange rate. Since the currency market is volatile and susceptible to ongoing social and political events, the proposed model incorporates event sentiments to accurately predict the exchange rate. Moreover, as the currency market is heavily dependent upon highly volatile factors such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 54 publications
0
14
0
1
Order By: Relevance
“…All the experiments were carried out with Python on AMD processor A8-7410 APU with AMD Radeon R5 Graphics with 8GB RAM. We have used accuracy as an evaluation metric in this research work [25,[28][29][30][31]. The proposed methods are evaluated over 2 datasets under different cooperative and strict covariate conditions.…”
Section: B Results and Discussionmentioning
confidence: 99%
“…All the experiments were carried out with Python on AMD processor A8-7410 APU with AMD Radeon R5 Graphics with 8GB RAM. We have used accuracy as an evaluation metric in this research work [25,[28][29][30][31]. The proposed methods are evaluated over 2 datasets under different cooperative and strict covariate conditions.…”
Section: B Results and Discussionmentioning
confidence: 99%
“…Other studies were aimed at predicting stock prices given textual information from the financial news [44][45][46]. For instance, Akita et al [44] converted newspaper articles into distributed representations via paragraph vectors and modeled the temporal effects of past events with an LSTM on predicting opening prices of stocks on the Tokyo Stock Exchange.…”
Section: Feature Selection For Stock Price Predictionmentioning
confidence: 99%
“…The study concluded that Twitter data could be used to predict the direction of exchange rate change. Yasir et al [7] conducted a sentiment analysis using a Twitter dataset and investigated the impact of Twitter on the exchange rate. In this study, both exchange rates and oil and gold prices were examined as numerical data.…”
Section: Literature Reviewmentioning
confidence: 99%